Relevansi Investasi Ala Rosulullah Di Era Modernisasi - Dewi Riza Lisvi Vahlevi (Universitas Muhammadiyah Jember, 2023)
In achieving our good financial dreams in the future, of course we can't just rely on the funds sitting in our savings accounts. Apart from not providing high profits, it can also cause the value of our money to be eroded by inflation. Therefore, it is recommended by financial experts to divert it to investment instruments. But there is a dilemma that Muslims might feel about contemplating whether the investments they are currently making are in accordance with Islamic law. This research uses a qualitative descriptive method, by reviewing investments that are correct and in accordance with what was taught by Rasulullah SAW and its relevance in this modern era. So that people no longer hesitate to invest and can also improve their economy in the future.